Candida albicans infection model in Drosophila melanogaster suggests a strain-specific virulent factor boosting a stormy innate immune response - Cortacans, Mariona; Arch, Marta; Fuentes, Esther; Cardona, Pere-Joan (Frontiers in Immunology, 2024)
The Drosophila melanogaster experimental model allows to evaluate the role of innate immunity to control infections. In this study we have tested its capacity to modulate systemic infections with a clinical and a control ATCC 90028 Candida albicans strains. To do so, we have primed flies with oral administration of heat-killed C. albicans (hkCa), both clinical and control, and hk-Mycolicibacterium manresensis. Both treatments showed a significant capacity to enhance the expression of antimicrobial peptides, in particular Diptericin, and Drosomycin in males. This response had a marked sexual dimorphism due to the difference in Upd3, Nox, and Duox expression. Surprisingly, even when priming was able to avoid the growth of both C. albicans strains, survival was not improved in the case of the clinical isolate, causing an unexpected mortality rate in hours, regardless of the host’s sex. Gene expression analysis 24 hours post-infection showed an exacerbated increase in Diptericin, Drosomycin and Upd3 expression upon infection with the clinical strain. Data herein suggests the presence of a strain-specific component in C. albicans as the booster of a “stormy” innate immune response, which must be further investigated, and position D. melanogaster as a useful model for evaluating virulent factors related to the modulation of the innate immunity.